Digital Activism in the Omnibus Law Discourse Network Structure and the Role of Hashtags in Mobilizing Public Opinion - Nora Titahning Ayudha (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2022)
The Omnibus Law is one of the biggest polemics in the socio-political calendar in 2020. For its supporters, the ratification of the Omnibus Law is an entry point for investment in Indonesia, while the opposition believes that this policy has a negative impact on exploiting natural resources and labor. This study focuses on the network structure, both social and textual, that was formed during the Omnibus Law discourse and the work of Hashtags within the framework of digital activism. This research combines descriptive qualitative research with Social Network Analysis (SNA) and Textual Network Analysis (TNA) methods with Netlytic software in collecting data and Wordji and Gephi. Data collection was carried out during September 26 to October 3 and received 1521 tweets. The results of this study indicate that civil organizations and socio-political activists are the dominant actors in voicing the public interest. The Hashtag #batalkanomnibuslaw became the most dominant phrase. Various Hashtags that show rejection of the ratification of the Omnibus Law have also become phrases that dominate in several conversations. Influential actors state that Hashtags are reducing the information complexity and need to be combined with direct organization in the real world so that it can influence public policy.